Governor Generals' House - Thomas, H.O. (H.O. Thomas, Trinidad, 2009)
Colour; Coloured; Style: Landscape; Other: Unbordered, Undivided
A view of the Royal Botanical Gardens just in front of Governor's Residence with a variety of colourful tropical flora, the flag of Trinidad and Tobago flies at full staff on top of the main building and the green rolling hills of St. Ann's fill the background. This residence is known today as "The President's House". The postcard is addressed to Mr. and Mrs. Alfred Platt, Cobleskill, New York, U.S.A. Affixed to the postcard is a Trinidad and Tobago 12 cents stamp, postmarked February 19, 1963.
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historical buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Flags--Trinidad and Tobago; 1963; Plants, Ornamental--Trinidad and Tobago; President's House, The